It’s Easier to Reach Heaven than the End of the Street: A Jerusalem Memoir By Emma Williams (Northampton, MA: Olive Branch Press, 2010. 415 pages.) (American Journal of Islam and Society, 2010)
Emma Williams is a British doctor who studied history at Oxford andmedicine at London. This book, which was first published in Britain in2006, records her experiences and assessments of what she saw when she accompanied her husband, a senior UN official, to Israel during 2000-03.The family lived in Jerusalem’s “Forest of Peace,” an area south of the oldcity, which remained undeveloped because it had been no man’s landpatrolled by the UN between 1948 and 1967. Emma and her husband wentwith three children and had a fourth, born out of choice in a Palestinianhospital in Bethlehem, while they were there. Her husband spent much ofhis time in Gaza; Emma worked in Jerusalem and, when possible, in theWest Bank ...